Urbanonyms of anthroponymic origin on the map of modern Kharkiv - Удовенко, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2020)
Purpose. The purpose of the article is to determine the features of the functioning of urbanonyms in modern Kharkiv. Research methodology. Methods. The analysis of urbanonyms constitutes a number of methodological problems associated with the difficulties of generalizing and evaluating various data that reveal the internal heterogeneity of urbanonyms as a component of toponymy (urbanonyms). Urbanonym is primarily a linguistic phenomenon. The study is based on the classification of urbanonyms, built on the basis of two principles, morphological and semantic, which is common in linguistics. In the article, the author combines the analysis of urbanonyms and the processes of creating a new name with the study of the linguistic specificity of street names, using linguistic analysis, which involves the identification of a specific language unit, the identification of all its signs. Also, the author of the article used general scientific research methods: analysis and comparison. The scientific novelty of the study. For the first time in Ukrainian linguistics, a linguistic analysis of urbanonyms of anthroponymic origin was carried out, their word-formation specificity and social and cultural factors influencing the functioning of urbanonyms were studied. Conclusions. Kharkiv toponymy is a complex of special models of word formation of different productivity. The most productive way of forming Kharkiv toponyms is morphological. Other ways of formation of Kharkiv toponyms are inefficient. In the toponymy of Kharkiv there are names in the form of an adjective, based on which an anthroponym appears, but not all of them are formed from the names and surnames of people, but from those objects, in due time had in names these names or surnames. The Russian language was a feature of the official Kharkiv toponymy According to the author of the article, some of the names in Ukrainian at different times in the history of Kharkiv rangel from 3% to 8%. In Kharkiv for a long time there were, and some still exist, grammatically incorrect names. The name should always be based on the characteristic feature of the nomination. As evidenced by the facts of the last renaming, carried out in 2015‒2016, according to the requirements of the Law of Ukraine “on condemnation of the Communist and national socialist (Nazi) totalitarian regimes in Ukraine and the prohibition of propaganda of their symbols” in Kharkiv, several hundred inner-city objects were renamed, new names of which are provided with varying degrees of correctness. The results can be used to prepare special courses in regional onomastics, historical studies of local lore and urban studies, as well as in educational and cultural work.